« La fille de la pêcheuse » dans le réseau des essais féministes de Le Guin - Irène Langlet (ReS Futurae)
Le Guin’s career is mostly presented through the novel cycles. The essayist work is much less often commented on in France. "The Fisherwoman’s Daughter", a major essay that will be here a pivotal argument for the reading of a series of feminist essays by Le Guin, shows the culmination of a fifteen-year journey. The Woolfian heritage leads to a re-reading of the novel The Left Hand of Darkness as marked by an "ambiguous feminism", and to reconsider the feminist inscription in the light of the feminine one, whose articulation with the literature of genre has much more complexity than some simplifying speech claims. "The Fisherwoman’s Daughter", on the contrary, promotes a demanding feminism, aware of its progressivity, critical of feminism as much as of patriarchy when creation and procreation are disarticulated.